Priceless - Woods, Sherryl (Mira Ontario Don Mills, 2004)
Return to the heart of the Carlton family in this beloved story of finding love in unexpected places by #1 New York Times bestselling author Sherryl Woods Charismatic playboy Mack Carlton lit up a room--even a hospital room--like no one else. Dr. Beth Browning had to admit Mack's visits were a tonic for her young patient, but her own reaction was much more confusing... Although Beth didn't ask for a second opinion on her future with Mack, his aunt Destiny offered her prognosis: marriage. Given Mack's romantic history and her own wariness due to past losses, Beth hesitated to agree--but her symptoms were undeniably love!
Keywords: Women Physicians -- Fiction; Man - Woman relationships -- Fiction